Low Diastolic Blood Pressure Predicts Depression in End Stage Renal Disease Patients on Maintenance Haemodialysis - Othman, Zahiruddin; Ismail, Siti Zubaidah; Saring, Ahmad Rasidi M; Jamaluddin, Ruzita (Japan International Cultural Exchange Foundation, 2014)
Aim: This study aimed to measure the prevalence and identify the predictors of depression in end stage renal disease (ESRD) patient on maintenance haemodialysis (HD). Methods: A 6-month cross-sectional study from December 2012 to May 2013 was conducted in nephrology unit, Hospital Sultanah Bahiyah and 3 private dialysis centres in Alor Setar, Kedah during the study period. Depression was assessed during the first hour of dialysis procedure in all participants using the Beck Depression Inventory (BDI). Results: A total of 91 patients were studied. The prevalence of depression was 19.8% with BDI cut-off score of 11. Lower diastolic blood pressure (P = 0.035) and presence of heart disease (P = 0.043) or stroke (P = 0.043) were found to be significantly associated with depression in ESRD patients on maintenance HD. None of the socio-demographic or laboratory parameters, including serum albumin, urea and hemoglobin, were signifícantly associated with depression. Conclusion: Depression is common and affecting about one-fifth of ESRD patients on HD. Hence, it is important to regularly assess the patients for depression giving particular attention to those with low diastolic blood pressure and co-morbid heart or cerebrovascular diseases.